THE INFLUENCE OF PRICE DISCOUNT, BONUS PACK, AND IN-STORE DISPLAY ON IMPULSE BUYING DECISION IN HYPERMART KAIRAGI MANADO - Waani, Rivie C. T.; Tumbuan, Willem J.F. Alfa (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Impulse buying is an unplanned purchase or spontaneous behavior which a shopper makes but has not planned in advance. This happens in consumers who will shop which carry out the purchase decision of goods in the store without planned it. Impulse buying can be affected from any kind of promotion conducted by a retail store. This research object is to know the influence of price discount, bonus pack, and in-store display on impulse buying decision. The sample of this research is consumers who make shopping in Hypermart Kairagi Manado on weekend around 2pm–9pm, as many as 90 respondents. The method used is Multiple Regression Analysis. Ftest and ttest used to determine simultaneous influence and partial influence of all independent variables to dependent variable. The result shows that price discount, bonus pack, and in-store display have significant influence on impulse buying decision simultaneously. Bonus pack and in-store display have significant influence partially on impulse buying decision while price discount has partial influence but no significant on impulse buying decision. Hypermart Kairagi Manado should maintain and improve the marketing strategies which is sales promotion in terms of promotional tools especially to price discount in order to attract more consumers make an impulse buying. Keywords: price discount, bonus pack, in-store display, impulse buying